Foragers, fishers and farmers: origins of the Taiwanese Neolithic. (December 2014) - Hung, Hsiao-chun; Carson, Mike T.
Abstract : The Neolithic of Taiwan represents the first stage in the expansion of Austronesian-speaking peoples through the Pacific. Settlement and burial evidence from the Tapenkeng (TKP) or Dabenkeng culture demonstrates the development of the early Taiwanese Neolithic over a period of almost 2000 years, from its origin in the pre-TPK of the Pearl River Delta and south-eastern coastal China. The first TPK communities of Taiwan pursued a mixed coastal foraging and horticultural lifestyle, but by the late TPK rice and millet farming were practised with extensive villages and large settlements. The broad-spectrum subsistence diversity of the Taiwanese Neolithic was an important factor in facilitating the subsequent expansion of Austronesian-speaking peoples to the Philippines and beyond.